Effect of single walled carbon nanotube addition to the physical properties of monolithic alumina - Ahmad Azhar, Ahmad Zahirani; Kahlib, Nor Amyra Zulianey; Manshor, Hanisah; Wee, Sing Yeo; Mohd Ali, Afifah; Rejab, Nik Akmar; Ahmad, Zainal Arifin (UR Publishers, 2018)
The effect of single-wall carbon nanotube (SWCNT) addition on the physical properties of alumina (Al2O3) ceramic composite were studied in this paper. The SWCNT and Al2O3 nanocomposite samples were prepared using wet mixing with 5 different compositions of SWCNT. The nanocomposite samples were confined inside alumina sagger with high purity graphite packing powder and were sintered using pressureless sintering at 1600°C. The hardness shows an optimum values at 0.1 wt% of SWCNT, 20.13 GPa. However, further addition of SWCNT then reduced the properties values of the Al2O3.